Pittosporum undulatum Vent.: subsidies to the control and management - Negrelle, Raquel Rejane Bonato; Mielke, Erica Costa; Cuquel, Francine Lorena; Pulido, Edwin Ernesto (Ornamental Horticulture, 2018)
Pittosporum undulatum (Australian cheesewood) is considered an ornamental species with high invasive potential, due to its strong adaptation capacity to colonize different habitats. Aiming to support controlling management actions, a review of its botanical, ecological, ethnobotanical and silvicultural aspects are presented. Control programs should include this type of information to ensure that the limited resources devoted to this issue will be efficiently allocated. It is important to address holistically the causes of the invasion, particularly the role of the original structure and functional changes imposed on ecosystems and their processes, since colonization by invasive species.